Komponenty nástrojov business intelligence - Klapáková, Katarína
Konkrétne komponenty nástrojov BI. Business Process (BP). Business Process Execution Language (BPEL). Business Process Modeling (BPM). Collective Intelligence (CI). Content Management System (CMS). Customer Relationship Management (CRM). Design Patterns. Enterprise Service Bus (ESB). e-Learning / LMS (Learning Management System). Event-Driven Architecture (EDA). Model-Driven Architecture (MDA). Object-Relational Mapping (ORM).